Ruptured abdominal aortic aneurysm in Marfan's syndrome. Issue 742 (August 1987) - Lafferty, K.; McLean, L.; Salisbury, J.; Cotton, L. T.
Abstract : A rare case of ruptured abdominal aortic aneurysm in Marfan's syndrome is described. The patient was treated successfully with a straight aortic tube graft. Histology of the aneurysm wall showed changes typical of cystic medial necrosis.